KEPUASAN DAN LOYALITAS PELANGGAN AMING COFFEE: EXPERIENTIAL MARKETING - BELLA BELLINDA; EVA DOLOROSA; DEWI KURNIATI (Jurnal Bisnis dan Akuntansi, 2020)
Aming Coffee is a coffee shop that is very well known by coffee connoisseurs in Pontianak. Over time, Aming coffee tried to get closer to the connoisseurs of Aming coffee by presenting a more modern appearance of the booth to provide comfort for the connoisseurs by increasing customer satisfaction and loyalty. However, with the number of coffee shops popping up in recent years, it is very influential for Aming coffee with the emergence of similar business competition, so this is a threat for Aming to continue to maintain satisfaction for its consumers. This study aims to analyze the effect of experiential marketing on Aming Coffee customer satisfaction and loyalty and the influence of satisfaction on Aming Coffee customer loyalty in Pontianak. This study used a questionnaire method with 150 respondents taken by purposive sampling at two Aming Coffee locations. Data analysis using SEM-PLS, WarpPLS 6.0 software. The results of this study indicate that experiential marketing variables significantly influence customer satisfaction and customer loyalty. The customer satisfaction variable mediates the effect of experiential marketing on customer loyalty. Customer satisfaction is the most influential factor in experiential marketing which can ultimately lead to customer loyalty. There needs to be an increase in all aspects of experiential marketing (sense, feel, think, act, relate) to support Aming Coffee to be a comfortable gathering place for visitors, especially young people and able to give prestige to visitors.